Late Venous Thoracic Outlet Syndrome After Anatomic Fixation of a Diaphyseal Clavicle Fracture: A Case Report. Issue 1 (January 2021) - Fogel, Nathaniel; Lee, Jason T.; Bishop, Julius A.
Abstract : Case: We report the case of a 29-year-old man with a displaced mid-diaphyseal clavicle fracture that healed in anatomic position without fracture callus after surgical treatment but developed symptoms of late venous thoracic outlet syndrome (TOS) 19 months postoperatively. He was diagnosed with proximal subclavian vein thrombosis and was treated with urgent thrombolysis and staged first rib resection with resolution of symptoms. Conclusions: Late venous TOS is a potential complication of clavicle fracture, even in the setting of anatomic reduction and primary bone healing. This entity has previously only been described in the setting of nonunion and malunion.